Optimization Of Branding And Digital Marketing: Innovative Strategies to Improve The Competitiveness of Small and Medium Enterprises P roducing Banana Chips (In The Village of Pakenjeng) - Auladinnursoba, Alvi; Hibatul Azizi, Moch Farhan (Fakultas Kewirausahaan Universitas Garut, 2024)
This research aims to optimize the branding and digital marketing of UMKM Banana Chips